The sweet taste of success: The presence of glucose in the oral cavity moderates the depletion of self-control resources. - Hagger, Martin; Chatzisarantis, N. (Sage Publications, Inc., 2013)
According to the resource-depletion model, self-control is a limited resource that is depleted after a period of exertion. Evidence consistent with this model indicates that self-control relies on glucose metabolism and glucose supplementation to depleted individuals replenishes self-control resources. In five experiments, we tested an alternative hypothesis that glucose in the oral cavity counteracts the deleterious effects of self-control depletion. We predicted a glucose mouth rinse, as opposed to an artificially sweetened placebo rinse, would lead to better self-control after depletion. In Studies 1 to 3, participants engaging in a depleting task performed significantly better on a subsequent self-control task after receiving a glucose mouth rinse, as opposed to participants rinsing with a placebo. Studies 4 and 5 replicated these findings and demonstrated that the glucose mouth rinse had no effect on self-control in nondepleted participants. Results are consistent with a neural rather than metabolic mechanism for the effect of glucose supplementation on self-control.